First Report of a Multicenter Prospective Registry of Cranioplasty in the United Kingdom and Ireland. Issue 3 (September 2021) - Fountain, Daniel M; Henry, Jack; Honeyman, Susan; O'Connor, Paul; Sekhon, Priya; Piper, Rory J; Edlmann, Ellie; Martin, Michael; Whiting, Gemma; Turner, Carole; Mee, Harry; Joannides, Alexis J; et al.
Abstract : BACKGROUND : There are many questions that remain unanswered regarding outcomes following cranioplasty including the timing of cranioplasty following craniectomy as well as the material used. OBJECTIVE : To establish and evaluate 30‐d outcomes for all cranial reconstruction procedures in the United Kingdom (UK) and Ireland through a prospective multicenter cohort study. METHODS : Patients undergoing cranioplasty insertion or revision between June 1, 2019 and November 30, 2019 in 25 neurosurgical units were included. Data collected include demographics, craniectomy date and indication, cranioplasty material and date, and 30‐d outcome. RESULTS : In total, 313 operations were included, consisting of 255 new cranioplasty insertions and 58 revisions. Of the new insertions, the most common indications for craniectomy were traumatic brain injury (n = 110, 43%), cerebral infarct (n = 38, 15%), and aneurysmal subarachnoid hemorrhage (n = 30, 12%). The most common material was titanium (n = 163, 64%). Median time to cranioplasty was 244 d (interquartile range 144‐385), with 37 new insertions (15%) within or equal to 90 d. In 30‐d follow‐up, there were no mortalities. There were 14 readmissions, with 10 patients sustaining a wound infection within 30 d (4%). Of the 58 revisions, the most common reason was due to infection (n = 33, 59%) and skin breakdown (n = 13, 23%). In 41 (71%) cases, the plate was removed during the revision surgery. CONCLUSION : This study is the largest prospective study of cranioplasty representing the first results from the UK Cranial Reconstruction Registry, a first national registry focused on cranioplasty with the potential to address outstanding research questions for this procedure. Graphical Abstract : Figure. Graphical Abstract